Meta-analysis and cost effective analysis of portal-superior mesenteric vein resection during pancreatoduodenectomy: Impact on margin status and survival. (March 2017) - Bell, Richard; Ao, Braden Te; Ironside, Natasha; Bartlett, Adam; Windsor, John A.; Pandanaboyana, Sanjay
Abstract: Introduction: The benefit of portal-superior mesenteric vein resection (PSMVR) with pancreatoduodenectomy (PD) remains controversial. This study assesses the impact of PSMVR on resection margin status and survival. Method: An electronic search was performed to identify relevant articles. Pooled odds ratios were calculated for outcomes using the fixed or random-effects models for meta-analysis. A decision analytical model was developed for estimating cost effectiveness. Results: Sixteen studies with 4145 patients who underwent pancreatoduodenectomy were included: 1207 patients had PSMVR and 2938 patients had no PSMVR. The R1 resection rate and post-operative mortality was significantly higher in PSMVR group (OR1.59[1.35, 1.86] p=<0.0001, and OR1.72 [1.02, 2.92] p = 0.04 respectively). The overall survival at 5-years was worse in the PSMVR group (HR0.20 [0.07, 0.55] P = 0.020). Tumour size (p = 0.030) and perineural invasion (P = 0.009) were higher in the PSMVR group. Not performing PSMVR yielded cost savings of 1617 per additional month alive without reduction in overall outcome. Conclusion: On the basis of retrospective data this study shows that PD with PSMVR is associated with a higher R1 rate, lower 5-year survival and is not cost-effective. It appears that PD with PSMVR can only be justified if R0 resection can be achieved. The continuing challenge is accurate selection of these patients.